«BRANCHING» OF WORLD CRISIS AND GREAT DEMAND OF HUMANE CRISISOLOGY AS A METATHEORY AND SOCIAL SCIENCES PHILOSOPHY - Aleksey M. Erokhin; Valeriy I. Kashirin (Вестник Северо-Кавказского федерального университета)
The need for judgments of crises as a specific social phenomenon grows. Crisisology turns from the historical science into the political and philosophical theory of global consequences of crises which gain more and more humanitarian character.